MELISOPALINOLOGY OF KLANCENG HONEY FROM 4 LOCATIONS IN KLATEN, MAGELANG, AND BOYOLALI DISTRICTS - Nurul Hidayati; Sri Widodo Agung Suedy; Kasiyati; Muh Samsudin (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2026)
Klanceng honey is a type of honey produced by stingless bees. The characteristics of klanceng honey are a liquid texture and a more sour or bitter taste. The content of honey is influenced by the honey's food source, which can be seen from the pollen contained in the honey. Identified pollen can be used to indicate the characteristics of the plants that serve as bee food sources. The purpose of this study was to determine the diversity of pollen sources in klanceng honey from Penggung Village, Boyolali Regency; Kebonrejo Village, Magelang Regency; Ceper Village, and Ngemplak Village, Klaten Regency, which can be used to identify plants that serve as bee food sources and be used to label honey based on its food source. The sampling method used exploratory sampling with purposive sampling. The pollen analysis method used acetolysis. Data analysis used descriptive analysis. The results of melisopalinology showed that there were 26 plant pollen families contained in the four klanceng honeys, with coconut (Cocos nucifera) pollen being the most dominant. Klanceng honey from Ceper and Kebonrejo villages is monofloral, while honey from Penggung village is bifloral, and honey from Ngemplak village is multifloral. The conclusion of this study is that the plant diversity of klanceng bees' food sources is diverse.